Case report: Pathological and genetic features of pancreatic undifferentiated carcinoma with osteoclast-like giant cells - Ni Zhao; Nan Mei; Ye Yi; Hongyan Wang; Yajian Wang; Yu Yao; Chunli Li (Pathology and Oncology Research, 2023)
Objectives: Pancreatic undifferentiated carcinoma accounts for 2%–7% of pancreatic carcinomas. We aimed to investigate the pathological and genetic characteristics of pancreatic undifferentiated carcinoma with osteoclast-like giant cells and the key points of treatment.Methods: The clinical data and follow-up results of four patients diagnosed with pancreatic undifferentiated carcinoma with osteoclast-like giant cells between May 2015 and May 2020 at the First Affiliated Hospital of Xi’an Jiaotong University were retrospectively analyzed.Results: Chief complaints included “pain and discomfort in the upper abdomen” (2/4), “nausea and vomiting” (1/4) or no symptoms (1/4). Preoperative mildly elevated tumor markers included carcinoembryonic antigen (1/4) and CA19-9 (1/4). The tumors were located in the tail of the pancreas in three patients and the head and neck in one patient. Tumor metastasis was found in pancreatic adipose tissue in two patients and lymph node metastasis in one patient, with microscopic heterogeneous mononuclear cells and scattered osteoclast-like giant cells of various sizes. One patient (1/4) had a mucinous cystic tumor of the pancreas, and two patients (2/4) had adenocarcinoma of the pancreatic duct. Only one patient received postoperative gemcitabine combined with albumin-bound paclitaxel chemotherapy.Conclusion: Currently, treatment guidelines are lacking for PUC-OGC, and prognosis varies markedly. More cases must be reported to clarify its origination. The long-term follow-up of diagnosed patients and genetic mutation testing can also contribute to improving treatment and prognosis of this disease.